2008
DOI: 10.1038/cr.2008.86
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by shikonin through a ROS/JNK-mediated process in Bcr/Abl-positive chronic myelogenous leukemia (CML) cells

Abstract: This study examined the signaling events induced by shikonin that lead to the induction of apoptosis in Bcr/ Abl-positive chronic myelogenous leukemia (CML) cells (e.g., K562, LAMA84). Treatment of K562 cells with shikonin (e.g., 0.5 μM) resulted in profound induction of apoptosis accompanied by rapid generation of reactive oxygen species (ROS), striking activation of c-Jun-N-terminal kinase (JNK) and p38, marked release of the mitochondrial proteins cytochrome c and Smac/DIABLO, activation of caspase-9 and -3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
153
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(172 citation statements)
references
References 39 publications
18
153
1
Order By: Relevance
“…Therefore, the anti-or pro-apoptotic effects of the MeK inhibitor on Ga-treated lung cells can be variable depending on cell type. in general, the activation of JnK or p38 leads to apoptosis (13)(14)(15). in fact, the JnK inhibitor was found to protect Pc12 rat phenochromocytoma against Ga-induced cell death (25), and the p38 inhibitor was found to decrease the death of pyrogallol-induced calf pulmonary artery endothelial cells (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the anti-or pro-apoptotic effects of the MeK inhibitor on Ga-treated lung cells can be variable depending on cell type. in general, the activation of JnK or p38 leads to apoptosis (13)(14)(15). in fact, the JnK inhibitor was found to protect Pc12 rat phenochromocytoma against Ga-induced cell death (25), and the p38 inhibitor was found to decrease the death of pyrogallol-induced calf pulmonary artery endothelial cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinases (MaPKs) are involved in cell proliferation, differentiation and cell death (12). Substantial evidence demonstrates that the c-Jun n-terminal kinase/stress-activated protein kinase (JnK/SaPK) and p38 are activated by roS, and oxidative stress leads to apoptosis (13)(14)(15). roS also are known to regulate the activation of the extracellular signal regulated kinase (erK1/2)-activating kinase (MeK) and erK (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…This indirectly suggests that the inhibition of erK signaling by MeK inhibitor plays a pro-survival role in Ga-treated calu-6 cells. Multiple lines of evidence demonstrate that JnK or p38 signaling is related to cell death (16,17). indeed, Ga was shown to induce Pc12 rat phenochromocytoma cell death through the activation of JnK, and JnK inhibitor protected Pc12 cells against Ga-induced cell death (25).…”
Section: Discussionmentioning
confidence: 99%
“…each MaP kinase pathway has relatively different upstream activators and specific substrates (15). Multiple lines of evidence demonstrate that JnK and p38 are strongly activated by roS or by a mild oxidative shift in the intracellular thiol/disulfide redox state, leading to apoptosis (16,17). roS are also known to induce erK phosphorylation and to activate the erK pathway (18).…”
mentioning
confidence: 99%
“…For instance, Mao et al (2008) reported that shikonin induced apoptosis through the ROS/ c-Jun N-terminal kinases (JNK)-mediated process in CML cell lines K562 and LAMA84. Rakshit et al (2010) reported the role of ROS in chlorogenic acid (Chi)-induced cell death in CML cell lines as well as primary leukemia cells from CML patients.…”
Section: Discussionmentioning
confidence: 99%